Dangerous desire : sexual freedom and sexual violence since the sixties - Barnett, Pamela E. (Routledge, 2004)
This is an important work that calls attention to how post-1960s literary representations of rape have shaped the ways in which both sexual and social freedoms are imagined in American literature and culture.